Risk taking and information aggregation in groups - Spiros Bougheas; Jeroen Nieboer; Martin Sefton (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2014)
We report an experiment examining risk taking and information aggregation in groups. Group members come to the table with an individual preference for a choice under risk, based on privately received information, and can share this information with fellow group members. They then make a decision under risk on behalf of the group using a random dictatorship mechanism, as well as an individual decision. Our analysis reveals that, while the behavior of many subjects is consistent with Bayesian rationality, a considerable number of subjects exhibited 'reverse confirmation bias': they place less weight on information from others that agrees with their private signal and more weight on conflicting information. We also observe a striking degree of consensus: in most groups all members made the same choice on behalf of the group. The pattern of individual choices after group deliberation suggests that the high degree of group consensus is due to persuasive arguments of other group members.
Keywords: C91; C92; D71; D80; 330; Group behavior; Teams; Decision Making; Risk; Experiment